Neuroprotective effects of the new Na channel blocker rs100642 in global ischemic brain injury - Suat Kamisli (Termedia Publishing House, 2019)
Introduction RS100642, a mexiletine analogue, is a novel sodium channel blocker with neuroprotective and antioxidant activities. The protectivity of RS100642, which has been shown against focal cerebral ischemia, was investigated in global cerebral ischemia in this study.